An experimental examination of interpersonal problem-solving in nonsuicidal self-injury: A pilot study. (December 2021) - Ammerman, Brooke A.; Sorgi, Kristen M.; Fahlgren, Martha K.; Puhalla, Alexander A.; McCloskey, Michael S.
Abstract: Nonsuicidal self-injury (NSSI) typically occurs in the presence of negative emotions. Prior research has emphasized interpersonal stress as a specific context that may elevate negative emotions in this population and even increase the likelihood of NSSI behavior. However, the factors that contribute to the relationship between interpersonal stress and NSSI have received relatively limited attention. The current pilot study aimed to experimentally examine interpersonal problem-solving as a potential moderator of the interpersonal stress – NSSI risk relationship among those with a NSSI history. Eighty-six participants (52.3% with NSSI history) were randomly assigned to one of three mood induction conditions (interpersonal negative, general negative, interpersonal neutral), after which they completed an interpersonal problem-solving task and a laboratory analogue of self-injurious behavior. Results indicated that NSSI history was associated with poorer interpersonal effectiveness. Further, individuals with a history of NSSI who experienced an interpersonally-focused negative mood and produced less effective interpersonal solutions were more self-harming on a laboratory analogue of self-injurious behavior. While the present findings are preliminary in nature, they offer guidance for research moving forward and, if replicated, suggest interpersonal problem-solving as a potential treatment target among individuals engaging in NSSI.